PERLINDUNGAN HUKUM BAGI USAHA MIKRO, KECIL DAN MENENGAH TERHADAP PRAKTIK PREDATORY PRICING DALAM PERSAINGAN USAHA DI E-COMMERCE - Zidni Ilma Muhammad (2022)
This research was conducted to analyze and study legal protection for domestic MSMEs against business competition in e-commerce, and also analyze and study predatory pricing by foreign entrepreneurs in business competition in e-commerce associated with Law Number 5 Year 19999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. Because in this digital era, people's attitudes and lifestyles have changed to become more sensitive to any changes, economic actors are increasingly creative, active and productive. One form of this awareness is the development of a new economy or what is popularly known as the creative economy or industry, therefore micro, small and medium enterprises (MSMEs) have penetrated into the digitalization era, selling online through digital platforms. Digitizing MSMEs has become one of the solutions for MSME actors, which are very large in number in Indonesia. However, the existing laws and regulations do not clearly regulate the legal protection of business actors who carry out their business activities in the digital market or E-Commerce from the practice of selling at a loss or predatory pricing in digital markets or e-commerce. This research uses normative and qualitative juridical research methods. The results of the discussion of this research are that there are regulations regarding selling at a loss or predatory pricing, but in the digital market or e-commerce sector, the clarity is still unclear, therefore article 20 of Law No. 5 of 1999 which regulates selling at a loss is still not enough to regulate the practice of selling at a loss or predatory pricing carried out in digital markets, especially on e-commerce platforms.